Great minds of the Eastern intellectual tradition - Hardy, Grant (Chantilly, VA : Teaching Co. : Great Courses, 2011)
Western philosophy is a vast intellectual tradition, the product of thousands of years of revolutionary thought built up by a rich collection of brilliant minds. When most of us study philosophy, we're focusing only on the Western intellectual tradition brought about by people such as Aristotle, Descartes, and Nietzsche. But to understand the Western intellectual tradition is to only get half of the story. Just as important, and just as valid a contribution to philosophy, is the Eastern intellectual tradition. Eastern philosophy is also the product of thousands of years of thought and was also built up by a distinct group of brilliant thinkers. Among these are Buddha, Confucius, Gandhi, and Zarathustra. Their ideas demonstrate fascinating, wholly different ways of approaching, understanding, and solving the same fundamental questions that concerned the West's greatest thinkers, such as the existence of God, the meaning of life, the nature of truth and reality, the organization of government and society, the significance of suffering, and the roots of a well-lived life. To explore Eastern perspectives on these issues is to embark on an illuminating journey into the heart of grand, but often unfamiliar, civilizations. It's also a thought-provoking way to understand the surprising connections and differences between East and West, and to strengthen your knowledge of cultures that play increasingly important roles in our globalized 21st-century world.
Grant Hardy, University of North Carolina, Ashville, lecturer
Keywords: Intellectual life -- History; Philosophers; Philosophy, Asian